A Comparison of Doppler Flow Parameters in the Ophthalmic Artery and Central Retinal Artery in Patients With Graves' Disease and Toxic Nodular Goiter - Walasik-Szemplińska, Dorota; Kamiński, Grzegorz; Mańczak, Małgorzata; Widłak, Joanna; Sudoł-Szopińska, Iwona (Frontiers in Endocrinology, 2019)
Purpose: Despite unquestionable clinical usefulness of Clinical Activity Score, the evaluating system needs frequent supplementation. One of such diagnostic tools is Doppler imaging that is used for the analysis of flow in the retrobulbar vessels. The improvement of the reliability and sensibility of measurements could make Doppler imaging an everyday clinical tool and improve the efficacy of treatment in patients with active thyroid-associated orbitopathy. However, the systemic influence of hyperthyroidism on the orbital vessels can falsify the assessment of local inflammation severity. Methods: To eliminate the influence of systemic hyperthyroidism on orbital vessels, we compared peak systolic velocity (PSV), end-diastolic velocity (EDV), and resistance index (RI) in the central retinal artery (CRA) and ophthalmic artery (OA) in patients with hyperthyroidism in the course of Graves’ disease without any detectable orbital changes, (CAS=0) and toxic nodular goiter. Results: There were no statistically significant differences between the patients with Graves’ disease and toxic nodular goiter in terms of the examined parameters in either of the arteries. However, higher PSV and RI and lower EDV in the CRA as well as higher PSV and EDV and unchanged RI in the OA were found in the patients with Graves’ diseases and toxic nodular goiter. Conclusion: Hyperthyroidism and hyperthyroidism-induced hyperkinetic flow have a systemic influence on the orbital vessels, irrespective of the cause of hyperthyreosis. Thus, it is necessary to compare the flow parameters in retrobulbar vessels in Graves’ patients with the toxic nodular goiter patients to eliminate the systemic influence of hyperthyroidism on the orbital vessels.